"Smoked Yankees" and the Struggle for Empire : Letters from Negro Soldiers, 1898-1902 - Gatewood, Willard B., Jr. (Willard Badgett), 1931- (University of Arkansas Press reprint series, 1987)
"Called upon for the first time to render military service outside the States, Negro soldiers (called Smoked Yankees by the Spaniards) were eager to improve their status at home by fighting for the white man in the Spanish-American War. Their story is told through countless letters sent to black U.S. newspapers that lacked resources to field their own reporters. The collection constitutes a remarkably complete and otherwise undisclosed account of the black man's role in -- and attitude toward -- America's struggle for empire."--